An evaluation of instructional management in three selected Dominican-owned schools in Region VI - Catoera, Remia T., O.P. (Animo Repository, 1995)
This study covers the comprehensive evaluation of the instructional management of the three selected Dominican-owned schools in Region VI using Stufflebeam's Context-Input-Process-Product (CIPP) evaluation model. The schools are Mary Immaculate Academy of Calinog, Sacred Heart Academy of Zarraga, and St. Jerome Academy of Duenas. A random sample consisting of 43 teachers, 7 subject area coordinators, 1 assistant principal, and 3 principals were included in the study. The study showed that the Mission Statements, goals, and objectives of the Dominican-owned schools generally embodied the Congregation's mission of evangelization through their school. In general, the instructional program of the Dominican-owned schools was implemented in accordance with the instructional management objective and the school's mission, philosophy, and objectives. Instructional management concerns were generally in the area of material resources, not in human resources. The root cause of almost all of the instructional problems in the respondent schools was the inability of the school administrators to provide the necessary budget for its implementation. Lastly, instructional management in the respondent schools was found to be moderately satisfactory. Based on the results and the conclusions of the study, the following recommendations were given: Improvement of the formulation of objectives in quantifiable terms to sufficiently provide for an objective evaluation of the program in the future. Tap financial resources to fully support the objectives of instructional management in their schools. For each school, formulation of their mission statement, goals and objectives which capture their uniqueness, but deviating from the Dominican Congregation's mission. Dissemination of the findings serves as baseline data in developing a long-range, systematic instructional management program for each school. Offering of a seminar on the utilization of improvised materials for the laboratory teachers. Replication of the study in other Dominican-owned schools for greater results.